The Equus Datum and the Early Radiation of Equus in China - Sun, Boyang; Deng, Tao (Frontiers in Ecology and Evolution, 2019)
To approach a comprehensive understanding of the Equus Datum, we summarize the history of the study of Chinese fossil equids, from the “dragon bones” stage to scientific investigation, by Chinese, European and American people, and then review the stenonid species in China and discuss the phylogenetic relationships of early Equus. We conclude that there were at least two dispersal waves of Equus into the Old World from North America, and the second wave led to a radiation of the genus Equus in China. In China, the ages of the lower boundaries of the fossiliferous layers in classical Early Pleistocene faunal localities are all around 2.5 Ma (close to the age of the lower boundary of the Quaternary) according to magnetostratigraphic and biostratigraphic analyses. All of the geochronological results reveal China as an evolutionary center of Equus in Eurasia. In the late Neogene, the dominant equid lineage in China was Hipparionini. Even in the Pliocene, when hipparionines were not as widespread as before, there were still 5 genera and 7 species. In the Early Pleistocene, the hipparionines included only 2 genera and 2 species. In the meantime, global cooling caused Arctic ice sheets to form, lowering the sea level so that the Bering land bridge fell dry and allowed Equus to disperse into China. The rise of Equus was accompanied by the recession of hipparionines. The dispersal and radiation of Equus in China were not a coincidence, but a complicated process of adaptation and competition, and a comprehensive outcome of significant climatic, tectonic and biotic events.